2020
DOI: 10.1111/ctr.14186
|View full text |Cite
|
Sign up to set email alerts
|

Modifying dietary patterns in cardiothoracic transplant patients to reduce cardiovascular risk: The AMEND‐IT Trial

Abstract: Background Cardiovascular disease (CVD) is common after cardiothoracic transplantation and causes substantial morbidity. Aims To assess feasibility and potential effectiveness of dietary interventions to reduce CVD risk. Materials and Methods In a pilot intervention, we recruited patients from a tertiary hospital and randomly allocated them to a Mediterranean or low‐fat diet for 12 months. Feasibility was measured by patient participation, retention, and adherence. Changes in weight, body mass index (BMI), hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“… 26 Cholesterol and triglyceride levels decreased with both diets. 26 Likewise, among 42 Italian HTRs followed‐up for 48 months, those who adhered to dietary advice reduced weight and lipids, while those who did not increase weight and lipids at 12 and 48 months. 21 Similar beneficial effects on weight and blood lipids were observed after a 6‐month lifestyle intervention.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“… 26 Cholesterol and triglyceride levels decreased with both diets. 26 Likewise, among 42 Italian HTRs followed‐up for 48 months, those who adhered to dietary advice reduced weight and lipids, while those who did not increase weight and lipids at 12 and 48 months. 21 Similar beneficial effects on weight and blood lipids were observed after a 6‐month lifestyle intervention.…”
Section: Discussionmentioning
confidence: 92%
“…While the primary approach to treating dyslipidaemia in HTRs is through medications, dietary approaches favorably combat lipid and weight increases 21 . In a UK feasibility study, 41 thoracic transplant recipients were randomly allocated to either a Mediterranean or low‐fat diet for 12 months, and showed weight reduction in the former (−1.8 kg), negligible weight gain in the latter (.2 kg), but 2‐kg gain in those who did not participate 26 . Cholesterol and triglyceride levels decreased with both diets 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a dietary intervention study among thoracic transplant recipients in England, baseline diet was found to be low in fruit and vegetables 8 . In the same study, the weight of HTRs decreased slightly after 12 months of dietary intervention, whereas the weights of control HTRs who did not participate in the study, increased 9 . Similarly, in a study of US HTRs at least 12 months post‐transplantation, 50% (14/24) were consuming high‐fat diets (≥ 37% energy from fats) and significantly increased their mean weight (73 kg pre‐transplant to 83 kg 12 months post‐transplant p < 0.05) 10 .…”
Section: Introductionmentioning
confidence: 93%
“…8 In the same study, the weight of HTRs decreased slightly after 12 months of dietary intervention, whereas the weights of control HTRs who did not participate in the study, increased. 9 Similarly, in a study of US HTRs at least 12 months post-transplantation, 50% (14/24) were consuming high-fat diets (≥ 37% energy from fats) and significantly increased their mean weight (73 kg pretransplant to 83 kg 12 months post-transplant p < 0.05). 10 Dietary studies of other organ transplant recipient groups have also shown low adherence to recommended diets, with subsequent weight increase.…”
Section: Introductionmentioning
confidence: 97%